308. Secondary Infections in Patients Requiring Extracorporeal Membrane Oxygenation (ECMO) for Severe Acute Respiratory Distress Syndrome (ARDS) due to COVID-19 Pneumonia (PNA). (4th December 2021) - Rivosecchi, Ryan; Viehman, J Alex; Thorngren, Christina K; Shields, Ryan K; Silveira, Fernanda P; Silveira, Fernanda P; Kwak, Eun Jeong; Volpe, Peter; Jagadeesan, Vidya; Clancy, Cornelius J; Nguyen, Minh Hong; Samanta, Palash
Abstract: Background: Rescue ECMO has been used worldwide in patients (pts) with ARDS caused by COVID-19. Bacterial super-infections affect 3.5-14.3% of hospitalized pts with COVID-19. Pts requiring ECMO may be at an increased risk of infection due to their severity of illness, gut translocation and ECMO impact on host immunity. Methods: This was a retrospective review of pts requiring ECMO for COVID-19 from April 2020-2021 at a single center. Strict definitions of infections (including ventilator-associated PNA, VAP) were in accordance with CDC criteria. Results: 43 ECMO pts with 1065 ECMO days were evaluated. Median age was 53 yrs (range: 21-62) and median BMI was 36.2 (range: 19.4-75.8). 70% were men and 65% were white. 37 patients (86%) experienced a total of 40 infectious episodes with a median onset from ECMO cannulation to first infection of 10.5d (range: 4-50). Median SOFA and SAPSII scores at time of infection were 12 (6-20) and 63 (30-90), respectively. PNA was the most common infection (78%, with 19% of cases complicated by bacteremia and 3% by empyema) (Fig. 1). The most common organisms isolated were Enterobacterales (37%), S. aureus (25%) and P. aeruginosa (16%) (Fig. 2). Only 2% of all organisms were multi-drug resistant. 3 pts had fungal infections (1 candidemia, 2 aspergillus PNA). Duration of ECMO was significantly longer for infected pts (26d, range: 5-92d) vs (11d, range: 3-24d), p=.01. 95% of infected pts had received steroids vs. 67% of uninfected pts, p=0.09. Treatment success at 1 week was 50%, and 24% and 40% of pts had recurrent infections and persistent/recurrent organisms in clinical cultures, respectively. S. aureus (54%) and Enterobacterales (26%) were associated with persistent or recurrent clinical cultures, requiring prolonged antimicrobial therapy. Mortality rate at 30 days was 65% and was significantly higher for pts with infection than those without (67% vs 33%, p=.02). Conclusion: Super-infection (most commonly PNA) occurred in almost all COVID-19 pts requiring ECMO for >4 days, and was a significant risk factor for death. Recurrent infections among survivors were common, especially when caused by Enterbacterales or S. aureus . Super-infection and mortality rates of ARDS pts on ECMO for COVID-19 were worse than for ARDS pts on ECMO for influenza at our center. Disclosures: Ryan K. Shields, PharmD, MS, Shionogi (Consultant, Research Grant or Support) Fernanda P. Silveira, MD, MS, FIDSA, Ansun (Individual(s) Involved: Self): Grant/Research Support; Novartis (Individual(s) Involved: Self): Grant/Research Support; Qiagen (Individual(s) Involved: Self): Grant/Research Support; Shire (Individual(s) Involved: Self): Advisor or Review Panel member, Grant/Research Support; SlieaGen (Individual(s) Involved: Self): Grant/Research Support; Whiscon (Individual(s) Involved: Self): Grant/Research Support Cornelius J. Clancy, MD, Merck (Grant/Research Support)